People Conditions from Socio-economic and Health Aspects on Access to Improved Drinking Water in East Nusa Tenggara Province - Gabriel Otan Apelabi; Daniel Putra Pardamean Mbarep; Ratih Nurjayati; Iman Harisma Saleh Sasto; Yovita Yasintha Bolly (School of Postgraduate Studies, Diponegoro Univer, 2023)
TThe dynamics in access to improved drinking water in East Nusa Tenggara province from 2017 to 2021 can also happen to the people's conditions. This study aims to determine the potential dynamics in people's conditions from socioeconomic (education and poverty rates) and health (diarrheal disease rate) aspects and their relationship with access to improved drinking water. The dynamics of people's conditions are analyzed based on the calculation of the annual average percentage of the education, poverty, and diarrheal disease rates using a comparative descriptive analysis method. Then to access improved drinking water, it is calculated and analyzed using the linear regression analysis method. The first result is an increase in the education rate of the people as has occurred in access to improved drinking water, but there has been a decrease in poverty and diarrheal disease rates. Other results also show a significant relationship with access to improved drinking water, as evidenced by a significance F-value of 0.0315. This shows the dynamics in people's conditions and interrelated/mutually impacting each other with access to improved drinking water.